2018
DOI: 10.1007/s41030-018-0058-6
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Body Clock in Asthma and COPD: Implication for Treatment

Abstract: Asthma exhibits a marked time of day variation in symptoms, airway physiology, and airway inflammation. This is also seen in chronic obstructive pulmonary disease (COPD), but to a lesser extent. Our understanding of how physiological daily rhythms are regulated by the circadian clock is increasing, and there is growing evidence that the molecular clock is important in the pathogenesis of these two airway diseases. If time of day is important, then it follows that treatment of asthma and COPD should also be tai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 88 publications
1
34
0
1
Order By: Relevance
“…Growing evidence suggests cigarette smoking severely affects circadian rhythms, which may further contribute to its role in the cause and disease progression of COPD (for review, see Truong et al, 2016;Krakowiak and Durrington, 2018). Although the evidence is not currently well-established, it appears that cigarette smoke targets a multitude of COPD-related symptoms, which normally display their own circadian oscillations and vary in severity throughout the day.…”
Section: Hr Bpmmentioning
confidence: 99%
See 1 more Smart Citation
“…Growing evidence suggests cigarette smoking severely affects circadian rhythms, which may further contribute to its role in the cause and disease progression of COPD (for review, see Truong et al, 2016;Krakowiak and Durrington, 2018). Although the evidence is not currently well-established, it appears that cigarette smoke targets a multitude of COPD-related symptoms, which normally display their own circadian oscillations and vary in severity throughout the day.…”
Section: Hr Bpmmentioning
confidence: 99%
“…Although the evidence is not currently well-established, it appears that cigarette smoke targets a multitude of COPD-related symptoms, which normally display their own circadian oscillations and vary in severity throughout the day. For example, exacerbation of mucus secretion and excessive coughing at Zeitgeber Time 04:00 h (i.e., early morning) are observed (Barnes, 1985; for review, see Sundar et al, 2015;Krakowiak and Durrington, 2018). Maintaining the coordination between the endogenous circadian clocks and exogenous light/dark cycles is pertinent for optimizing all aspects of mammalian physiology (for review, see Bechtold et al, 2010;Truong et al, 2016).…”
Section: Hr Bpmmentioning
confidence: 99%
“…Previous research [42] has shown that the circadian rhythm influences the severity of asthma symptoms. Symptoms tend to be worst around 4:00 am and gradually improve during the day.…”
Section: Discussionmentioning
confidence: 98%
“…This finding is consistent with asthma diurnal variation and should be taken into consideration when defining the time of at home measurements. Circadian variation in asthma causes lower spirometry measurements in the early morning hours when the disease is at its nadir 6 . A larger difference between mSpirometry and clinic measurements observed in the morning compared to afternoon/evening suggests the impact of FEV 1 diurnal variation rather than suboptimal efforts by…”
Section: Discussionmentioning
confidence: 99%
“…Asthma is characterized by airflow obstruction which displays a diurnal pattern. Diurnal variation is observed in lung function in healthy individuals 5 and is greater in asthma patients 6 . The lowest FEV 1 measurements are observed in early morning hours coinciding with increased symptoms and airway inflammation 7 .…”
Section: Introductionmentioning
confidence: 99%